2021
DOI: 10.3390/rs13204049
|View full text |Cite
|
Sign up to set email alerts
|

Combining Tracking and Remote Sensing to Identify Critical Year-Round Site, Habitat Use and Migratory Connectivity of a Threatened Waterbird Species

Abstract: We tracked 39 western flyway white-naped cranes (Antigone vipio) throughout multiple annual cycles from June 2017 to July 2020, using GSM-GPS loggers providing positions every 10-min to describe migration routes and key staging areas used between their Mongolian breeding and wintering areas in China’s Yangtze River Basin. The results demonstrated that white-naped cranes migrated an average of 2556 km (±187.9 SD) in autumn and 2673 km (±342.3) in spring. We identified 86 critical stopover sites that supported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 47 publications
3
20
0
Order By: Relevance
“…Since WNC breeding, wintering, and staging grounds stretch across a huge area and many countries, this can only be achieved through collaborative research efforts. Many of the WNCs key sites are unprotected 53 55 including breeding sites, which our study indicates have decreased in suitability and may be key in explaining the species’ population decline. Though we did not link habitat conditions directly to survival in this study, conditions were clearly associated with breeding performance and therefore likely long-term productivity.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Since WNC breeding, wintering, and staging grounds stretch across a huge area and many countries, this can only be achieved through collaborative research efforts. Many of the WNCs key sites are unprotected 53 55 including breeding sites, which our study indicates have decreased in suitability and may be key in explaining the species’ population decline. Though we did not link habitat conditions directly to survival in this study, conditions were clearly associated with breeding performance and therefore likely long-term productivity.…”
Section: Discussionmentioning
confidence: 82%
“…These climatic processes in combination with increasing human activity are expected to result in further degradation of wetlands in the region. Over the past 50 years, many of the region’s wetlands have been converted to agricultural land 75 – 77 , reducing breeding habitat but also opening up alternative foraging opportunities for WNCs 53 , 78 . The use of these fields by cranes is causing human-wildlife conflicts due to real or perceived crop damage in many places 26 , 77 , 79 83 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From 1991From to 1993 individuals in Japan and Russia were tracked to present the migration routes, stopover sites, and migration patterns (Higuchi et al 1992(Higuchi et al , 1996(Higuchi et al , 2004Ueta 2002). By the 2020s, a large amount of longterm tracking data revealed that the upper reaches of the Luanhe River in Inner Mongolia, China, comprised the most important stopover area for the western population of White-naped Cranes (Lang et al 2020;Batbayar et al 2021).…”
mentioning
confidence: 99%